The level of fear of Corona-Virus Disease (COVID-19) among citizens and its effect on SMSE in Lagos State - Falobi, Oluwole Victor; Ige, Lawrence Olusola; Olugbenle, Toyosi Sijuade; Dike, Christopher (Universitas Mercu Buana Yogyakarta, 2023)
The study assessed the level of fear of nimbus-contagion (Covid -19) among citizens and its effect on SMSE in Lagos State. The outbreak of the nimbus-contagion disease in Nigeria has increased the tension and anxiety among citizens. The researchers believe it could trigger some adverse effects on small and medium-scale enterprises in Lagos state. A descriptive research strategy was used for the study. A self-structured questionnaire, a four-point Likert scale, was used as the instrument for data collection. One Hundred (100) participants were aimlessly named as the sample size for the study. The questionnaire has sections; section A comprises demographic data of the participants, while section B was used to evoke responses from the participants grounded on the research questions. Analysis was done using frequency counts, percentage of chance, mean, and standard deviation, while T-test was used to test the two (2) hypotheses at 0.05 level of significance. The findings discovered that: the impact of corona-virus disease (COVID-19) on SMSE in Lagos State is high; it was also revealed that the level of fear of corona-virus disease (COVID-19) among citizens and the effect on SMSE in Lagos State is high. It was recommended that Measures should be put in place for the future occurrence of any pandemic; Online sales and services should be encouraged for business owners and consumers; the Company should encourage online engagement of clients than simple office calls; Saving culture should be encouraged for future purposes.